2022
DOI: 10.7759/cureus.24068
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder and Substance Use Disorder: A Narrative Review

Abstract: Attention deficit hyperactivity disorder (ADHD) has a growing incidence and prevalence in the United States and throughout the world, much of which is contributed to increased awareness of the condition and solidified diagnostic criteria. Substance use disorder (SUD) similarly has seen a sharp increase, particularly with the rising cases of opioid abuse. Management of ADHD is done primarily with pharmacologic therapy, often stimulants and with psychosocial interventions (i.e., exercise, meditation, peer-to-pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous literature reported that ADHD can persist into adulthood [ 39 , 40 ]. During adulthood, it impairs occupational function and work productivity [ 41 44 ], academic achievements [ 44 ], family and interpersonal relationships [ 45 ] and increases the risk of substance abuse [ 46 ]. Moreover, ADHD also increases economic burden on families and society [ 47 , 48 ].…”
Section: Introductionsmentioning
confidence: 99%
“…Previous literature reported that ADHD can persist into adulthood [ 39 , 40 ]. During adulthood, it impairs occupational function and work productivity [ 41 44 ], academic achievements [ 44 ], family and interpersonal relationships [ 45 ] and increases the risk of substance abuse [ 46 ]. Moreover, ADHD also increases economic burden on families and society [ 47 , 48 ].…”
Section: Introductionsmentioning
confidence: 99%